Water restriction scenarios and their effects on traits in potato with different degrees of drought tolerance - Lin, X.; Ramírez, D.; Qin, J.; Dormatey R.; Bi, Zhenzhen; Sun, C.; Wang, H.; Bai, J. (Elsevier, 2019)
The search for plant traits associated with drought tolerance for genetic improvement is an important issue in breeding acceleration programs. However, plant traits expression depends on the drought scenario, thus the investigation of this dependence is crucial for drought tolerant related traits selection in important crops like potato. In this study, six potato genotypes with contrasted drought sensitivity were submitted to a long- (LTWR) from flower budding formation until harvest and short-term (STWR, 4 cycles) water restriction and compared to irrigated condition (control). Indicators related to chlorophyll concentration increase (ChlSPAD_Amp), senescence delay (as slope of chlorophyll concentration declined, SlopeChl), oxidative defense and damage through superoxide dismutase, peroxidase (POD) and malonaldehyde (MDA) synthesis in comparison with control (△) were calculated and contrasted with a drought tolerance index (DTI). ChlSPAD_Amp, △MDA and SlopeChl explained 22–55%, 74–72% and 0–81% of DTI linear variation under STWR-LTWR respectively. Significant correlations were found only under LTWR, where oxidative damage and defense (specially △POD) were associated with ChlSPAD_Amp and SlopeChl. This study cautions the drought scenario-dependency of some traits related to senescence delay and oxidative defense-damage, whereas the stability of leaf greenness (taking care of high drought sensitive genotypes) invites further efforts using remote sensing technologies for their test in large panel breeding programs.